Risk factors for an anxiety disorder comorbidity among Thai patients with bipolar disorder: Results from the Thai Bipolar Disorder Registry - Suchat Paholpak (2018)
Background: The aim of the study was to determine in a clinical setting the risk factors for current anxiety disorder (AD) comorbidity among Thai patients with bipolar disorder (BD), being treated under the Thai Bipolar Disorder Registry Project (TBDR). Methods: The TBDR was a multisite naturalistic study conducted at 24 psychiatric units (ie, at university, provincial mental, and government general hospitals) between February 2009 and January 2011. Participants were in- or out-patients over 18 years of age who were diagnosed with BD according to the Diagnostic and Statistical Manual of Mental Disorders, Fourth Edition. Instruments used in this study included the Thai Mini International Neuropsychiatric Interview version 5; Thai Montgomery-Åsberg Depression Rating Scale (MADRS); Thai Young Mania Rating Scale; Clinical Global Impression of Bipolar Disorder-Severity (CGI-BP-S), CGI-BP-S-mania, CGI-BP-S-depression, and CGI-BP-S-overall BP illness; and the Thai SF-36 quality of life questionnaire. Results: Among the 424 BD patients, 404 (95.3%) had BD type I. The respective mean ± standard deviation of age of onset of mood disturbance, first diagnosis of BD, and first treatment of BD was 32.0±11.9, 36.1±12.2, and 36.2±12.2 years. The duration of illness was 10.7±9.0 years. Fifty-three (12.5%) of the 424 participants had a current AD while 38 (9%) had a substance use disorder (SUD). The univariate analysis revealed 13 significant risks for current AD comorbidity, which the multivariate analysis narrowed to age at first diagnosis of BD (odds ratio =0.95, P < 0.01), family history of SUD (odds ratio =2.18, P=0.02), and having a higher current MADRS score (odds ratio =1.11, P < 0.01). Conclusion: A diagnosis of AD comorbid with BD is suggested by early-age onset of BD together with a higher MADRS score and a family history of SUD. The likelihood of AD comorbidity decreases by 5% with each passing year; early-age onset of BD is a risk while later age onset is protective. Our results underscore how SUD within the family significantly contributes to the risk of an AD comorbidity. © 2014 Paholpak et al.